Unlocking greener supply chains: A global innovative perspective on the role of logistics performance in reducing ecological footprints - Haoyu Cheng; Hassan Rauf Chaudhry; Irfan Kazi; Muhammad Umar (Journal of Innovation & Knowledge)
One of the significant challenges to achieveing the Green Supply Chain Management objectives is the ecological footprint associated with several logistics operations. In this study, we examine the impact of countries' logistics performance on environmental quality. For this purpose, the study collected data from a panel of 43 global economies over the period of 2010–2016. We used a composite index of logistics performance (LPI) to evaluate logistics performance and the ecological footprint (EFP) to assess environmental quality across diverse countries. Our results indicate that improvements in logistics performance are significantly associated with reductions in ecological footprints after controlling the effects of GDP, imports, exports, and adjusted net national income. These results are promising, and our findings highlight that although LPI initially intends to track the logistics performance without any consideration to the environmental concerns, most of its dimensions are indirectly capturing these concerns. These results compel policymakers to pay special attention to logistics performance, which is undoubtedly one of the most significant segments of global supply chains and may have the potential to make these supply chains greener and more environmentally friendly.